PENGENDALIAN KEWAJIBAN PEMBUATAN SUMUR RESAPAN DI KECAMATAN BINA WIDYA OLEH DINAS PEKERJAAN UMUM DAN PENATAAN RUANG (PUPR) KOTA PEKANBARU TAHUN 2021 - Vieka Juniaty Putri; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is motivated by the rapid development of Pekanbaru City which is accompanied by the wider need for housing. This raises new environmental problems, one of which is the reduction of water catchment land which results in runoff water flooding. Therefore, efforts are needed to absorb more water into the soil. As stated in Pekanbaru City Bylaw number 10 of 2006 concerning Water Resources and Infiltration Wells which contains the obligation to make infiltration wells. In this Bylaw, it is contained about controlling the obligation to make infiltration wells in Article 27 paragraph 1. This study aims to see how the process of controlling the obligation to make infiltration wells, especially in RTT buildings and shophouses in Bina Widya District by the Pekanbaru City PUPR Office. In this study, the author used qualitative research methods, which were conducted by interviews with related informants, observations, and documentation. The results of this study show that based on several steps in the control process, the Determination of Standards related to the obligation to make infiltration wells is contained in Pekanbaru City Bylaw number 10 of 2006 then stated in Perwako number 8 of 2007 concerning Technical Guidelines for Infiltration Wells. In the performance measurement indicators of controlling the obligation to make infiltration wells, the Pekanbaru City PUPR Office has not been optimally carried out, as can be seen from the lack of people who obey the creation of infiltration wells. Furthermore, comparing the actual performance with the standards, the performance of the PUPR Office is still not effective in implementing this Bylaw. And on the indicators of determining the need for corrective action, corrective actions in controlling the obligation to make infiltration wells can be carried out by socializing the obligation to make infiltration wells, improving the performance of implementers supervising the obligations to make infiltration wells, and providing sanctions and compensation by violators of the obligation to make infiltration wells.. Keywords: Control, Infiltration Wells, Residential Houses and Shophouses